Minangkabau Ancient History and Cultural Communication - Bagindo, Muhammad Nur; Chaniago, Maizufri Ilyas; Herwandi, Herwandi; Muhammad Djamil, Purwohusodo; Hussin, Hanafi (Environment-Behaviour Proceedings Journal, 2023)
This study focuses on history and culture communication the Minangkabau kingdom that located on the island of Sumatra, Indonesia. This kingdom covers the central part of the island of Sumatra. The Minangkabau Malay kingdom was centered on the Batanghari River. The purpose of this study is to explain the role of Minangkabau Malay in world trade and the results of cultural communication. The research method used is historical research methods through library and archive research. It turned out that the Ancient Minangkabau Malay Kingdom had opened cultural relations with India so that there were Hindu and Buddhist influences in Sumatra.